Premature atrial contractions: A predictor of atrial fibrillation and a relevant marker of atrial cardiomyopathy - Guichard, Jean-Baptiste; Guasch, Eduard; Roche, Frederic; Da Costa, Antoine; Mont, Lluís (Frontiers in Physiology, 2022)
The increased burden of premature atrial contractions has long been considered a benign phenomenon. However, strong evidence of its involvement in the occurrence of atrial fibrillation(AF), ischemic stroke, and excess mortality suggests the need for its management. The central question to be resolved is whether increased atrial excitability is only a predictor of AF or whether it is a marker of atrial cardiomyopathy and therefore of ischemic stroke. After reviewing the pathophysiology of atrial excitability and its impact on patient prognosis, this mini-review proposes to (i) detail the physiological and clinical elements linking atrial excitability and AF, (ii) present the evidence in favor of atrial excitability as a marker of cardiomyopathy, and (iii) outline the current limitations of this concept and the potential future clinical implications.